2023
DOI: 10.3389/fgene.2023.1083593
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of an angiogenesis-related lncRNA prognostic model in lung adenocarcinoma

Abstract: Background: There is increasing evidence that long non-coding RNAs (lncRNAs) can be used as potential prognostic factors for cancer. This study aimed to develop a prognostic model for lung adenocarcinoma (LUAD) using angiogenesis-related long non-coding RNAs (lncRNAs) as potential prognostic factors.Methods: Transcriptome data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) were analyzed to identify aberrantly expressed angiogenesis-related lncRNAs in LUAD. A prognostic signature was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In lung carcinomas, differential expression of lncRNAs has been observed depending on the cancer type. Representative cases are SLC9A3-AS1, reported upregulated; LINC01554 and GABPB1 reported downregulated in NSCLC tissues [166][167][168], while RBPMS-AS1 expression was found to be diminished in lung adenocarcinoma [169]. Other studies have shown the reduced expression of LINC00294 in colorectal carcinoma tissues [170], while SLFNL1-AS1, KCNQ1OT1, NEAT1, XIST, AC016876.2, AC026362.1 were found to be downregulated in colon cancer cell lines [171].…”
Section: Discussionmentioning
confidence: 96%

miRNAs as Interconnectors between Obesity and Cancer

González-Sánchez,
Granados-López,
López-Hernández
et al. 2024
ncRNA
“…In lung carcinomas, differential expression of lncRNAs has been observed depending on the cancer type. Representative cases are SLC9A3-AS1, reported upregulated; LINC01554 and GABPB1 reported downregulated in NSCLC tissues [166][167][168], while RBPMS-AS1 expression was found to be diminished in lung adenocarcinoma [169]. Other studies have shown the reduced expression of LINC00294 in colorectal carcinoma tissues [170], while SLFNL1-AS1, KCNQ1OT1, NEAT1, XIST, AC016876.2, AC026362.1 were found to be downregulated in colon cancer cell lines [171].…”
Section: Discussionmentioning
confidence: 96%

miRNAs as Interconnectors between Obesity and Cancer

González-Sánchez,
Granados-López,
López-Hernández
et al. 2024
ncRNA
“…Results of risk analysis suggested that LINC00968, LINC00663, and ITGA9-AS1 have the potential to serve as anti-tumor regulators in LUAD, conversely, LINC00857 was identified as a risk factor. LINC00857 has been extensively associated with tumor invasion 28 , angiogenesis 29 , glycolysis 30 , immune infiltrating 31 , 32 , apoptosis, and autophagy 33 , and its prognostic predictive performance has been widely demonstrated in solid tumors. The overexpression of LINC00857 reduced the survival time of patients through controlling miR-1179/SPAG5 axis 30 , and its oncogenic roles have been revealed in colorectal and pancreatic cancer cells 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The identification of Notch/MAPK-related genes is important for elucidating the molecular mechanisms involved in high-risk ccRCC. To develop a model with advantages over other reported sAR-lncRNA predictive models 37 , 38 , we first identified 4 potential lncRNA-genes/-proteins associated with ccRCC prognosis. Notably, MAP3K12 and PLA2GB participate in angiogenic processes.…”
Section: Discussionmentioning
confidence: 99%